Women’s Job Search Competence: A Question of Motivation, Behavior, or Gender - Llinares-Insa, Lucía I.; González-Navarro, Pilar; Córdoba-Iñesta, Ana I.; Zacarés-González, Juan J. (Frontiers in Psychology, 2018)
We examined motivation and behaviors in women’s active job search in Spain and the gender gap in this process. The current crisis in Spain and the increase in the number of unemployed people have revealed new inequalities that particularly affect women’s employability, especially the most vulnerable women. This paper addresses two exploratory studies: the first study analyzes gender differences in the active job search using a sample of 236 Spanish participants; the second study explores the heterogeneity and diversity of unemployed women in a sample of 235 Spanish women. To analyze the active job search, the respondents were invited to write open-ended responses to questions about their job search behaviors and complete some questionnaires about their motivation for their active job search. The content analysis and quantitative results showed no significant differences in motivational attributes, but there were significant gender differences in the job search behavior (e.g. geographical mobility). Moreover, the results showed heterogeneity in unemployed women by educational level and family responsibilities. The asynchronies observed in a neoliberal context reveal the reproduction of social roles, social-labor vulnerability, and a gender gap. Thus, women’s behavior is an interface between employment and family work, but not their motivations or aspirations. Our results can have positive implications for labor gender equality by identifying indicators of effectiveness in training programs for women’s job search, and it can contribute to designing intervention empowerment policies for women.